Hollywood: A Very Short Introduction - Decherney, Peter (New York Oxford University Press, 2016)
Hollywood: A Very Short Introduction is filled with discussions of well-known movies, stars, and directors, encapsulating the past century of research on Hollywood while adding many original insights and stories. It is the perfect introduction for readers who want to better understand the history and functioning of our screen-saturated world.
Includes Index and Illustrations.
Keywords: Motion picture industry